2017
DOI: 10.1371/journal.pone.0170011
|View full text |Cite
|
Sign up to set email alerts
|

Different Phenotypes of the Two Chinese Probands with the Same c.889G>A (p.C162Y) Mutation in COCH Gene Verify Different Mechanisms Underlying Autosomal Dominant Nonsyndromic Deafness 9

Abstract: ObjectivesBy analyzing the different phenotypes of two Chinese DFNA9 families with the same mutation located in the intervening region between the LCCL and vWFA domains of cochlin and testing the functional changes in the mutant cochlin, we investigated the different pathogeneses for mutations in LCCL and vWFA domains.MethodsTargeted next-generation sequencing for deafness-related genes was used to identify the mutation in the proband in family #208. The probands of family #208 and family #32 with the same p.C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Targeted genomic sequencing including 134 nuclear genes, three miRNA and three mitochondrial genes known to be responsible for NSHL or syndromic hearing loss (Table S1, supporting information), was performed in proband (III‐10), as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted genomic sequencing including 134 nuclear genes, three miRNA and three mitochondrial genes known to be responsible for NSHL or syndromic hearing loss (Table S1, supporting information), was performed in proband (III‐10), as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Targeted genomic sequencing including 134 nuclear genes, three miRNA and three mitochondrial genes known to be responsible for NSHL or syndromic hearing loss (Table S1, supporting information), was performed in proband (III-10), as previously described. 23,24 Whole exome capture was performed with the NimbleGen SeqCap EZ Exome 64 Mb V3 (Roche-NimbleGen, Madison, Wisconsin) according to the manufacturer's protocol. The qualified genomic DNA sample was randomly fragmented into 200 to 300 bp.…”
Section: Targeted Genomic Capture and Whole Exome Sequencingmentioning
confidence: 99%
“…After full-text screening, 48 studies met the eligibility criteria and together reported on 27 different COCH variants ( Figure 1 and Figure S1 ). Thirty-seven of these studies were retrospective family studies, describing the (audiovestibular) phenotype of COCH variants [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Eleven of the included studies were not primarily genotype-phenotype studies but validation studies of genetic analyses or histopathological studies [ 9 , 56 , 57 , 58 , 59 , 60 , 61 , 62...…”
Section: Resultsmentioning
confidence: 99%
“…The number of subjects with other pathogenic variants in COCH , and thus the amount of available phenotypic data, is much smaller. The audiometric evaluations of these subjects are therefore prone to selection bias, especially because inter-and intrafamilial variation is known to occur in DFNA9 [ 23 , 26 , 29 , 35 , 39 , 52 ]. In studies with large numbers of included subjects, as is the case for the p.(Pro51Ser) variant, the influence of selection bias decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Since ACAN-D2 was found in heterozygosity in one Mangalarga Marchador horse, despite the small number of sampled animals, we suggest that the potential association between ACAN:c.6465A > T (RefSeq XM_005602799.2-EquCab3.0) and dwarfism in Miniature horses would continue to be relevant; moreover, ACAN:c.6465A > T has provided population, genetic, and informatics prediction evidence that it could be a potential causative variant of dwarfism in this breed 22 . Indeed, a mutation may not always cause the same effects, or it may lead to different phenotypes of the same disorder in different individuals 23,24 . Several genetic modifiers can produce unexpected phenotypes of the primary disease-causing variant 25 , and the genetic background of Miniature horses and Shetland ponies, which were selected for diminutive size over the www.nature.com/scientificreports/ years, differs from horses of large breeds [26][27][28][29] and may generate a predisposition to the condition characterized as dwarfism due to ACAN variants.…”
Section: Discussionmentioning
confidence: 99%